2014
DOI: 10.1063/1.4871780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed Ge/Si cross-linking on the physical properties of amorphous Ge-Si-Te networks

Abstract: Amorphous GexSixTe1−2x glasses are studied as a function of composition by a combination of experimental and theoretical methods, allowing for a full description of the network structure in relationship with physico-chemical properties. Calorimetric and thermal measurements reveal that such glasses display an anomalous behavior across a range of compositions xc1=7.5% and <x<xc2=9%, in which is manifested a deep minimum in molar volume, non-reversing enthalpy, and liquid fragility. These anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 122 publications
(169 reference statements)
2
35
0
Order By: Relevance
“…absence of stress [352]), which manifests by a minimum in the molar volume ( Fig. 40a and c), a salient feature that has been reported for various systems [15,41,42,43,314,330,349,354]. The stress-free nature of such RWs has been detected from pressure experiments [352] showing the vanishing of a threshold pressure (Fig.…”
Section: Alternative Signatures Of Rwsmentioning
confidence: 67%
See 2 more Smart Citations
“…absence of stress [352]), which manifests by a minimum in the molar volume ( Fig. 40a and c), a salient feature that has been reported for various systems [15,41,42,43,314,330,349,354]. The stress-free nature of such RWs has been detected from pressure experiments [352] showing the vanishing of a threshold pressure (Fig.…”
Section: Alternative Signatures Of Rwsmentioning
confidence: 67%
“…Using MD simulations, the number of topological constraints has been investigated as a function of temperature in a certain number of glass-forming systems such as GeSe 2 [320], Ge-Te [315], Ge-Si-Te [314] or SiO 2 -2SiO 2 [279,311,316]. Figure 34 shows the analysis for 300 K and 1050 K for GeSe 2 , using either an average count (left) or indiviual constraints giving the distribution f(σ) (right) [320].…”
Section: Behavior In the Liquid Phasementioning
confidence: 99%
See 1 more Smart Citation
“…This situation contrasts with the Si-Te binary which contains a large fraction of SiTe 4/2 tetrahedra reminiscent of the local structure of the crystalline Si 2 Te 3 polymorph [126] which is 100% tetrahedral. In the ternary Ge-Si-Te system [124], the calculated tetrahedral fraction is found to be somewhat lower (33.7%) when compared to its isovalent compound (Ge 20 Te 80 , 54.6%) but is very close to the one determined experimentally from Mössbauer spectroscopy (40.8%). The detail of the numerical analysis permits to determine the different contributions, and it is found that Si sites dominate the population of tetrahedra (42.74% for Si against 24.6% for Ge).…”
Section: Quantifying Tetrahedramentioning
confidence: 73%
“…The detection and quantification of tetrahedral germanium can be made from angular standard deviations which are associated with BB interactions [123,124]. The method offers, indeed, the advantage to focus on angular excursions rather than working directly on angles [115].…”
Section: Quantifying Tetrahedramentioning
confidence: 99%